From Decoding Turbulence to Unveiling the Fingerprint of Climate Change Klaus Hasselmann-Nobel Prize Winner in Physics 2021 - von Storch, Hans (Springer Nature, 2022)
This open access book serves as a reference for the key elements and their significance of Klaus Hasselmann's work on climate science and on ocean wave research, all based on a rigorous and deeply physical thinking. It summarizes the original articles (mostly from the 1970 and 1980s; some of which are hard to find nowadays) and brings them in a present-day context. From 1975 until 2000, he was (founding) Director of the Max Planck Institute of Meteorology, which he made to one of the world-leading academic institutions. He first made the issue of anthropogenic climate change accessible to analysis and prediction and later transformed climate science into a significant factor in forming public policy. The book is written by co-workers and colleagues of Klaus Hasselmann, who-many under his immediate supervision-joined him in this effort. With this background, they present the key achievements and assess the significance of these for the present state of knowledge and scientific practice.